Epcam, CD44, and CD49f distinguish sphere-forming human prostate basal cells from a subpopulation with predominant tubule initiation capability. - Changyong Guo; Haibo Liu; Bao-Hui Zhang; Radu M Cadaneanu; Aqila M Mayle; Isla P Garraway (PLoS ONE, 2012)
Background Human prostate basal cells expressing alpha-6 integrin (CD49f(Hi)) and/or CD44 form prostaspheres in vitro. This functional trait is often correlated with stem/progenitor (S/P) activity, including the ability to self-renew and induce differentiated tubules in vivo. Antigenic profiles that distinguish tubule-initiating prostate stem cells (SCs) from progenitor cells (PCs) and mature luminal cells (LCs) with less regenerative potential are unknown. Methodology/principle findings Prostasphere assays and RT-PCR analysis was performed following FACS separation of total benign prostate cells based upon combinations of Epcam, CD44, and/or CD49f expression. Epithelial cell fractions were isolated, including Epcam(+)CD44(+) and Epcam+CD44+CD49f(Hi) basal cells that formed abundant spheres. When non-sphere-forming Epcam(+)CD44(-) cells were fractionated based upon CD49f expression, a distinct subpopulation (Epcam(+)CD44(-)CD49f(Hi)) was identified that possessed a basal profile similar to Epcam(+)CD44(+)CD49f(Hi) sphere-forming cells (p63(+)AR(Lo)PSA(-)). Evaluation of tubule induction capability of fractionated cells was performed, in vivo, via a fully humanized prostate tissue regeneration assay. Non-sphere-forming Epcam(+)CD44(-) cells induced significantly more prostate tubular structures than Epcam(+)CD44(+) sphere-forming cells. Further fractionation based upon CD49f co-expression identified Epcam(+)CD44(-)CD49f(Hi) (non-sphere-forming) basal cells with significantly increased tubule induction activity compared to Epcam(+)CD44(-)CD49f(Lo) (true) luminal cells. Conclusions/significance Our data delineates antigenic profiles that functionally distinguish human prostate epithelial subpopulations, including putative SCs that display superior tubule initiation capability and induce differentiated ductal/acini structures, sphere-forming PCs with relatively decreased tubule initiation activity, and terminally differentiated LCs that lack both sphere-forming and tubule-initiation activity. The results clearly demonstrate that sphere-forming ability is not predictive of tubule-initiation activity. The subpopulations identified are of interest because they may play distinct roles as cells of origin in the development of prostatic diseases, including cancer.